Factors Affecting the Saving Behaviour of Individuals - Pant , Dinesh Kumar (Researcher CAB: A Journal for Research and Development, 2024)
Savings refer to the portion of income that people do not spend right away but instead set aside for investments, future spending, or unplanned expenses. A study was conducted to analyze the factors affecting the saving behavior of individuals living in Birendra Nagar Surkhet, Nepal. The study considered marital status, income status, and financial literacy as independent variables, and saving behavior as the dependent variable. The data was collected using a structural questionnaire based on the convenience sampling method, and 190 responses out of 225 questionnaires distributed were observed. A multivariate regression technique was used to analyze the collected data. The study found that marital status and financial literacy had a significant effect on saving behavior, while income status and lifestyle had an insignificant effect. The study emphasized the importance of raising individuals' financial literacy in Birendra Nagar Surkhet, as it could have a favorable impact on their saving behavior.Saving behaviour